b)
3
x
+3
x+2
<270
3
x
+3
2
∗3
x
<270
3
x
+9∗3
x
<270
10∗3
x
<270 ∣:10
3
x
<27
3
x
<3
3
x<3.
ответ: x∈(-∞;3).
h)
\4*4^x-2\geq 7*2^x\\4*(2^2)^x-7*2^x-2\geq 0\\4*2^{2x}-7*2^x-2\geq 0\\\
4∗4
x
−2≥7∗2
x
4∗(2
2
)
x
−7∗2
x
−2≥0
4∗2
2x
−7∗2
x
−2≥0
Пусть 2ˣ=t ⇒
\4t^2-7t-2\geq 0\\4t^2-8t+t-2\geq 0\\4t*(t-2)+(t-2)\geq 0\\(t-2)*(4t+1)\geq 0\\(2^x-2)*(4*2^x+1)\geq 0\\4*2^x+1 > 0\ \ \ \ \Rightarrow\\2^x-2\geq 0\\2^x\geq 2\\2^x\geq 2^1\\x\geq 1.\
4t
2
−7t−2≥0
4t
2
−8t+t−2≥0
4t∗(t−2)+(t−2)≥0
(t−2)∗(4t+1)≥0
(2
x
−2)∗(4∗2
x
+1)≥0
4∗2
x
+1>0 ⇒
2
x
−2≥0
2
x
≥2
2
x
≥2
1
x≥1.
ответ: x∈[1;+∞).
х²-6х+9=-х²+2х+3
2х²-8х+6=0
D=64-48=16
x₁=(8+4)/4=3
x₂=(8-4)/4=1 получили пределы интегрирования
₃
S=∫₁ ((-x²+2x+3)-(x²-6x+9))dx= (-x²+2x+3-x²+6x-9)dx=(-2x²+8x-6)dx=
-2x³ 8x² ³ 2x³ ³ 2*3³ 2*1³
= + - 6x |= - + 4x²-6x | = - +4*3²-6*3 -( +4*1²-6*1)=
3 2 ₁ 3 ₁ 3 3
= -18+36-18-((-2/3)+4-6)=-((-2/3)-2)=-(-8*3)=8/3≈2,67